Pengaruh Konservatisme Akuntansi dan Manajemen Laba Terhadap Nilai Perusahaan dengan GCG sebagai Pemoderasi - Ardifarah, Khalisha Dhiya; Fitranita, Vika (Akuisisi : Jurnal Akuntansi, 2025)
The aim of this research is to analyze the influence of accounting conservatism and earnings management on company value, with moderation from good corporate governance. The population of this research is Manufacturing Companies in the food and beverage sub-sector from 2018-2022 and the data was obtained from the annual report on the official website of the Indonesia Stock Exchange (BEI). Data analysis used PLS-SEM with SmartPLS 4.0 software. The research results show that accounting conservatism has a positive and significant influence on company value, as well as earnings management. While good corporate governance moderation weakens the relationship between accounting conservatism and earnings management, it has a significant influence on firm value. Suggestions for further research are adding other sectors, adding research periods, adding proxies to moderating variables, and adding control variables using company probability to produce more in-depth, valid and reliable findings in supporting the development of science and company management practices.